Analisis Strategi Pembelajaran Alquran - Khoirul Bariyah Bariyah (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2021)
As a guide for humans in managing their lives in order to obtain physical and spiritual happiness, in this world and in the hereafter. To be able to learn and understand the content or content of the Qur'an is not easy, therefore the teacher or cleric must have a strategy, method or method in teaching it. The methods commonly used in an effort to be able to read the Qur'an properly and correctly in many TPQ or TPA include the Jibril, Bagdadi, Qiro'ati method, the Iqro method and the An-Nahdhiyah method. Among the stages of learning the Qur'an is by reading, translating and interpreting. As we know the first commandment when the Qur'an was revealed to the prophet Muhammad was reading, which of course has a very broad understanding. Then in another verse Allah SWT commands us to read the Qur'an with Tartil. In Abdullah bin Ahmad an-Nasafi's view "tartil" is to clarify the reading of all hijaiyah letters, maintain places to stop reading (waqaf), and perfect harokat. in reading. Meanwhile, Sayyidina Ali bin Abi Talib equated "tartil" with tajwid, namely improving the reading of the letters and knowing the stopping places (waqaf). In contrast to Ibn Kathir who interprets "tartil" as a slow reading that can help towards the level of understanding and contemplation of the Qur'an. In line with Ibn Kathir, Fakhrur Rozy in his commentary said "tartil" is to clarify and perfect the reading of all letters by giving all their rights by not hastily in reading the Qur'an.